2018
DOI: 10.7759/cureus.2713
|View full text |Cite|
|
Sign up to set email alerts
|

Pancreatic Cancer: Feasibility and Outcome After Radiochemotherapy with High Dose External Radiotherapy for Non-resected and R1 Resected Patients

Abstract: BackgroundNon-resected locally advanced and microscopic positive-margin resected (R1) pancreatic adenocarcinoma are associated with a dismal prognosis. The combination of high dose radiotherapy and concomitant chemotherapy is among the strategies that are used to improve the outcome. The aims of this study were to evaluate the acute and late toxicities and patients' outcome in a retrospective study from a single center.Material and methodsFrom 2009 to 2015, 24 patients, with non-resected locally advanced or R1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…PDAC recurrence rate after surgical resection is up to 60% in the first year, and 5-year survival of patients who underwent complete resection is only 25% (3). Nonsurgical therapies for PDAC include systemic chemotherapies (4-7), molecularly-targeted therapies (8), conventional ablative therapies (9)(10)(11)(12)(13), and radiotherapy (14)(15)(16)(17); however, they have so far offered little or no survival benefit (4,6,7,11,17).…”
Section: Introductionmentioning
confidence: 99%
“…PDAC recurrence rate after surgical resection is up to 60% in the first year, and 5-year survival of patients who underwent complete resection is only 25% (3). Nonsurgical therapies for PDAC include systemic chemotherapies (4-7), molecularly-targeted therapies (8), conventional ablative therapies (9)(10)(11)(12)(13), and radiotherapy (14)(15)(16)(17); however, they have so far offered little or no survival benefit (4,6,7,11,17).…”
Section: Introductionmentioning
confidence: 99%
“…The anatomical location of the pancreatic gland is close to many important organs, main arteries and veins. Consequently, a large proportion of patients with pancreatic carcinoma (80–85%) present with an extension to adjacent organs or distant metastases, rendering surgical resection 3. Currently, gemcitabine is recommended as the first-line drug for the treatment of advanced pancreatic cancer 4.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of radiotherapy is to promote tumor cell death. However, mounting publications have demonstrated that dying tumor cells can induce the accelerated regrowth of the resident cancer cells and form a special microenvironment for tumor recurrence [ [3] , [4] , [5] ], making the role of radiotherapy in treating of PC controversial [ 6 ].…”
Section: Introductionmentioning
confidence: 99%